If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(8y + -21) + 34 = 3 Reorder the terms: 2(-21 + 8y) + 34 = 3 (-21 * 2 + 8y * 2) + 34 = 3 (-42 + 16y) + 34 = 3 Reorder the terms: -42 + 34 + 16y = 3 Combine like terms: -42 + 34 = -8 -8 + 16y = 3 Solving -8 + 16y = 3 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + 16y = 3 + 8 Combine like terms: -8 + 8 = 0 0 + 16y = 3 + 8 16y = 3 + 8 Combine like terms: 3 + 8 = 11 16y = 11 Divide each side by '16'. y = 0.6875 Simplifying y = 0.6875
| 7.5X+11y=180 | | 23r=92 | | 4w-3(-5x+3w)-2x= | | 0=-10-14x+2y | | (5-u)(4u-6)=0 | | -7+a+2=12 | | 12x+24-18= | | 8(x-6)+18=3(2x-8) | | X+4x+10=90 | | 19b=290 | | 2b-8=24 | | 0.04(x-4)+0.06x=0.02x-0.01(60) | | 3.6-2.4m=11 | | 23-7y=58 | | 4(6x+1)+6=24x+10 | | x-(5+3x)+5x-(6+x)=-3 | | 2+2(x+5)=2(6x+5)-3(3x) | | -7-2p=9 | | 4(6x+10)=4(4x) | | 3x-1=3+1 | | 0.80x+0.85(40)=0.40(71) | | (x-3)(x-5(-1))(x+5(-1))=0 | | 21+(-5x+19)-(2x-3)+31=25-(4x-4)-(5x-3) | | (x-3)(x-5i)(x+5i)=0 | | (9x-2)+(5x+54)=180 | | 245=x+(245*0.06) | | 20+3y=53 | | 0.20(y-5)+0.16y=0.04y-0.01(60) | | 2x+5y=144 | | 3x-5x-(x+3)=8x+(-5x-9) | | 13x+182=156x | | 2x-0y=19 |